Accident proneness, or variable accident tendency? - Cresswell, W. L.; Froggatt, P. (Statistical and Social Inquiry Society of Ireland, 1962)
The term accident proneness is current in both medical and lay press, but it is not always used in the same sense, nor is one always confident that many who employ it so freely are aware of the exact assumptions contained in their definition To many, although not to all, the designation of a person as accident prone implies that, irrespective of environment, that individual is more likely at all times to incur an accident than his colleagues even though exposed to equal risk, and that this is due to some characteristic or summation of characteristics associated with corporeal dexterity, sensory-motor skill, personality, or higher conative or cognitive function. In short, accident proneness is conceived as an immutable load to which the unfortunate possessor is chained like some Ixion to his wheel. The corollary is that the population can either be dichotomised on the basis of the possession or non-possession of the characteristic, or at least ranked in terms of its severity.
Read before the Society, 26 March 1962
Keywords: Accident proneness; Variable accident tendency; Probability distributions; 314.15